Üniversite Öğrencilerinin Yaşam Anlamı ve Ruminatif Düşünce Biçimleri Arasındaki İlişkinin İncelenmesi - Kurtarankartal, Tülen (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
This research was conducted in the departments of English Language Teaching, Psychological Counseling and Guidance, Preschool Teaching, Special Education Teaching, Physiotherapy and Rehabilitation, Nutrition and Dietetics, Sports Sciences, Architecture and Interior Architecture. The aim of the study is to determine the relationship between the meaning of life and ruminative thinking levels of 4th and 4th grade students. The other aim of the research is; The aim of this study is to determine whether the meaning of life and ruminative thinking styles of university students differ significantly according to gender, class, department, traumatic life event, substance use and perceived parental attitude variables. The sample of the study consisted of 461 individuals, 249 of whom were women and 212 of which were men. Personal Information Form, Meaning of Life Scale and Ruminative Thinking Scale were applied to the participants. The data obtained from the study were analyzed by Pearson Product Moment Correlation Coefficient, t-test, One-Way ANOVA for the purposes of the study. As a result of the research, it was found that there is a positive meaningful relationship between “searched meaning olan which is the sub-dimension of life meaning of university students and ruminative thinking. In addition, it was found that the present meaning levels of university students differed significantly according to gender, grade level, substance use and perceived parental attitudes, and there was no significant difference according to department and traumatic life event. It was found that the ruminative thinking styles of university students showed a significant difference according to the variables of class level and department and did not show a significant difference according to gender, traumatic life event, substance use and perceived parental attitude variables. The findings of the research were interpreted and discussed in the light of the researches in the literature, and recommendations were made for researchers and practitioners. Keywords: Meaning of Life, Present Meaning, Ruminative Thinking, Rumination.

ÖZ: Bu araştırma, 2018-2019 bahar döneminde Doğu Akdeniz Üniversitesi’nin İngilizce Öğretmenliği, Psikolojik Danışmanlık ve Rehberlik, Okul Öncesi Öğretmenliği, Özel Eğitim Öğretmenliği, Fizyoterapi ve Rehabilitasyon, Beslenme ve Diyetetik, Spor Bilimleri, Mimarlık ve İç Mimarlık bölümlerinde öğrenim görmekte olan 1. ve 4. sınıf öğrencilerinin yaşam anlamı ve ruminatif düşünce biçimi düzeyleri arasındaki ilişkiyi belirlemeyi amaçlamaktadır. Araştırmanın diğer amacı ise; üniversite öğrencilerinin yaşam anlamı ve ruminatif düşünce biçimi düzeylerinin cinsiyet, sınıf, bölüm, travmatik yaşam olayı, madde kullanımı ve algılanan anne-baba tutumu değişkenlerine göre anlamlı bir farklılık gösterip göstermediğini ortaya koymaktır. Araştırmanın örneklemi, 249’u kadın, 212’si erkek toplam 461 kişiden oluşmaktadır. Araştırmaya katılan katılımcılara, Kişisel Bilgi Formu, Yaşam Anlamı Ölçeği ve Ruminatif Düşünce Biçimi Ölçeği uygulanmıştır. Araştırmadan elde edilen veriler, araştırmanın amaçları doğrultusunda Pearson Momentler Çarpımı Korelasyon Katsayısı, t-testi, Tek Yönlü Varyans Analizi (ANOVA) ile analiz edilmiştir. Yapılan araştırma sonucunda üniversite öğrencilerinin yaşam anlamı alt boyutu olan “aranan anlam” ile ruminatif düşünce biçimi arasında pozitif yönde anlamlı bir ilişkinin olduğu bulgulanmıştır. Ayrıca üniversite öğrencilerinin mevcut anlam düzeylerinin cinsiyet, sınıf düzeyi, madde kullanımı ve algılanan anne-baba tutumu değişkenlerine göre anlamlı olarak farklılaştığı, bölüm ve travmatik yaşam olayına göre anlamlı bir farklılığın olmadığı bulunmuştur. Üniversite öğrencilerinin ruminatif düşünce biçimi düzeylerinin ise sınıf düzeyi ve bölüm değişkenlerine göre anlamlı bir farklılık gösterdiği, cinsiyet, travmatik yaşam olayı, madde kullanımı ve algılanan anne-baba tutumu değişkenlerine göre anlamlı bir farklılık göstermediği tespit edilmiştir. Araştırma bulguları alan yazında yer alan araştırmalar ışığında yorumlanmış ve tartışılmış, araştırmacılara ve uygulayıcılara yönelik öneriler sunulmuştur. Anahtar Kelimeler: Yaşam Anlamı, Mevcut Anlam, Ruminatif Düşünce Biçimi, Ruminasyon.
Lisansüstü Eğitim, Öğretim ve Araştırma Enstitüsüne Rehberlik ve Psikolojik Danışmanlık Dalında Yüksek Lisans Tezidir. Tez (Yüksek Lisans)--Doğu Akdeniz Üniversitesi, Eğitim Fakültesi, 2019. Tez Danışmanı: Doç. Dr. Yeliz Akıntuğ.
Keywords: Rehberlik ve Psikolojik Danışmanlık; Yaşam Anlamı; Mevcut Anlam; Ruminatif Düşünce Biçimi; Ruminasyon; Meaning of Life; Present Meaning; Ruminative Thinking; Rumination